A one-pot electrochemical synthesis of 2-aminothiazoles from active methylene ketones and thioureas mediated by NH4I - Yang, Shang-Feng; Li, Pei; Fang, Zi-Lin; Liang, Sen; Tian, Hong-Yu; Sun, Bao-Guo; Xu, Kun; Zeng, Cheng-Chu (Beilstein Journal of Organic Chemistry, 2022)
The electrochemical preparation of 2-aminothiazoles has been achieved by the reaction of active methylene ketones with thioureas assisted by ᴅʟ-alanine using NH4I as a redox mediator. The electrochemical protocol proceeds in an undivided cell equipped with graphite plate electrodes under constant current conditions. Various active methylene ketones, including β-keto ester, β-keto amide, β-keto nitrile, β-keto sulfone and 1,3-diketones, can be converted to the corresponding 2-aminothiazoles. Mechanistically, the in situ generated α-iodoketone was proposed to be the key active species.
Keywords: 2-aminothiazoles; electrosynthesis; indirect electrolysis; halide ion